2015
DOI: 10.4103/0974-2727.163132
|View full text |Cite
|
Sign up to set email alerts
|

Renal Abscess Caused by Salmonella Typhi

Abstract: Salmonella typhi is a true pathogen, which is capable of causing both intestinal and extraintestinal infections. Unusual presentations of Salmonella should always be kept in mind as this organism can cause disease in almost any organ of the body. S. typhi has been reported to cause the life-threatening infections such as meningitis, endocarditis, myocarditis, empyema, and hepatic abscess. Renal involvement by S. typhi is a relatively rare presentation. We report a case of renal abscess caused by S. typhi in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Salmonella (NTS and typhoidal) infection commonly presents as gastroenteritis, invasive infection, or metastatic focal infection, but renal involvement, especially in the form of renal abscess, is rare. 8 - 12 , 15 A retrospective review done in Spain found only 1.4% of all infections due to NTS presenting as UTI. 16 Characteristics of patients with NTS isolated from the urine are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella (NTS and typhoidal) infection commonly presents as gastroenteritis, invasive infection, or metastatic focal infection, but renal involvement, especially in the form of renal abscess, is rare. 8 - 12 , 15 A retrospective review done in Spain found only 1.4% of all infections due to NTS presenting as UTI. 16 Characteristics of patients with NTS isolated from the urine are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“… 10 - 12 Renal abscesses are generally managed with antibiotics, with concomitant surgical intervention in some cases. 10 - 14 …”
Section: Introductionmentioning
confidence: 99%
“…However, there are reports of bacteria resistance to fluoroquinolones in developing countries. For this reason, treatment with third generation cephalosporins is an adequate alternative in these cases [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…serotypes pathogenic to human beings, the most common clinical disease being gastroenteritis [1,3]. Nevertheless, infections may occur in other sites out of the gastrointestinal tract, as well as may cause a septicemia [3]. Obstructions to urine drainage, like those caused by calculi, may lead to complications such as pyonephrosis, when urine becomes infected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation